Culture influence on Algerian Students’ EFL Writing An Insight into Teachers’ Practices - Haddad, Amina (Journal of Human Sciences, 2018)
The paper discusses a qualitative study that aims at exploring teachers’ perceptions and attitudes toward the role of culture in the foreign language writing class. It is based on the hypothesis that teachers of writing at the Ecole Normale Supérieure of Constantine (ENSC) have little awareness of the role of culture in the foreign/ second language writing class, that they have little knowledge of contrastive/ intercultural rhetoric, and that their teaching instruction (methodology, feedback, evaluation) does not reflect any culture consciousness or contrastive/ intercultural rhetoric use. To verify this hypothesis, interviews were conducted with three, experienced teachers of written expression at the department of English at the ENSC. Teachers’ responses have confirmed the aforementioned hypothesis.